Hounded - Rosenfelt, David (Rosenfelt, David. Andy Carpenter novels., 2014)
Andy Carpenter isn't sure what to think when he gets a mysterious phone call from a good friend, policeman Pete Stanton, asking him to drop everything, drive to an unfamiliar address, and bring his girlfriend, Laurie Collins. He certainly isn't expecting to show up at a crime scene. But that's exactly where he arrives<U+2014>at the house where Pete has just discovered the body of ex-convict Danny Diza. Upstairs are Danny's now orphaned eight-year-old son and basset hound. And that, Andy discovers, is why he and Laurie were called to the scene<U+2014>Pete wants them to take care of the boy and the dog so they won't get thrown into the "system." This is already asking a lot, but soon Pete needs another big favor from Andy. Pete himself has come under suspicion for Danny's murder, and he needs defense attorney Andy to represent him<U+2026>and to find out what really happened in Danny's house that day.